Memaknai Komunikasi Digital Secara Etis: Belajar dari Pemikiran Jürgen Habermas: Belajar dari Pemikiran Jürgen Habermas - Soekarba, Siti Rohmah; Widestomo Putra, Trassanda Scudetto (Respons: Jurnal Etika Sosial, 2024)
This article reconstructs Jürgen Habermas's conceptual apparatus—communicative action, four validity claims (truth, normative correctness, sincerity, comprehensibility), and discourse ethics—to ethically interpret algorithmically mediated digital communication. Using the Transcendental Dialectical Reconstruction Method combined with hermeneutic reading, critical discourse analysis, and instrumental case studies, this study builds a bridge from theory to practice through three main outputs: (1) a “Habermasian” evaluation matrix that translates the four validity claims into operational and auditable indicators; (2) a thought-experiment/fiction-based normative prototype useful for testing the ethical consistency of interface designs and platform policies; and (3) a domination-free design-governance guideline that normatively promotes reason-giving and demand-based approaches, substantive appeals, justification-based curation, and public explanation of algorithmic decisions. Application to the digital debate over the US-Indonesia “reciprocal” tariff policy demonstrates that procedural arrangements—a minimal reason format, a separation of fact-policy channels, reasoned moderation with an appeals path—can shift discourse from engagement metrics to open evaluation of reasons, while simultaneously reducing the tendency for the lifeworld to be colonized by system rationality. This article's primary contribution is a purely Habermas-based operationalization for the contemporary digital ecosystem, which strengthens discursive legitimacy through inclusive, transparent, and revisable procedures. Practical implications include a communication quality audit framework that researchers, educators, platform managers, and policymakers can adopt to advance Verständigung in the digital public sphere.